Holographic interferometry in experimental mechanics - Ostrovskii, IU. I. (IUrii Isaevich); Shchepinov, V. P. (Valeri P.), 1947-; Yakovlev, V. V. (Victor V.), 1920- (Berlin ; New York : Springer-Verlag)
Includes bibliographical references and index.